Enforcement of Economic, Social and Cultural Rights in Uganda A brief overview - Mbazira, Christopher (Economic and Social Rights in South Africa, 2009)
Uganda has ratified almost all the major regional and international instruments that protect economic, social and cultural rights (ESCRs). However, a reading of the Constitution of Uganda, 1995, and other laws shows that the rights have not been domesticated fully.